Prediction of Cracks Within Cones Processed by Single Point Incremental Forming - Guzman-Inostroza, C (Elsevier B.V., 2019)
Plane stress tests such as tensile tests on smooth and notched samples as well as shear tests are used to identify the set of material parameters associated with two damage models: a micromechanically-based Gurson model and a continuum Lemaitre and Chaboche model. Finite element simulations and inverse modelling are applied on these tests to characterize the mechanical behavior of a DC01 steel sheet. The capabilities of these two damage models to predict the maximum wall angle before failure of cones formed by single point incremental forming are analyzed, showing that the Lemaitre and Chaboche model appears to be more reliable when applied on this steel sheet. © 2019 The Authors. Published by Elsevier B.V.